2015
DOI: 10.1007/s13277-015-3131-x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of HABP1 is a novel prognostic indicator in triple-negative breast cancers

Abstract: Hyaluronan-binding protein 1 (HABP1) has been documented to overexpress in several malignancies. The aim of our study is to investigate the expression of HABP1 protein in triple-negative breast cancer (TNBC) and its clinical significance. Using immunohistochemistry, HABP1 expression was evaluated in 139 TNBC specimens. The association between HABP1 expression with clinicopathological parameters was assessed using chi-square test. The survival status of patients was analyzed using the Kaplan-Meier and log-rank … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…And we also found that HABP1 protein expression was an independent prognostic factor for breast cancer survival [17], especially for triple-negative breast cancer [16]. In the present study, we found that among the seven potential functional SNPs of the HABP1 gene, SNP rs2285747 was significantly associated with breast cancer risk and HABP1 protein expression in Chinese women of Heilongjiang Province.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…And we also found that HABP1 protein expression was an independent prognostic factor for breast cancer survival [17], especially for triple-negative breast cancer [16]. In the present study, we found that among the seven potential functional SNPs of the HABP1 gene, SNP rs2285747 was significantly associated with breast cancer risk and HABP1 protein expression in Chinese women of Heilongjiang Province.…”
Section: Discussionsupporting
confidence: 58%
“…Overexpression of HABP1 is observed in several cancers, such as lung, gastric, colon adenocarcinomas, epidermal carcinoma, ovarian cancer, and endometrial cancer [14, 15]. We previously found that the mRNA and protein levels of HABP1 significantly increased in breast cancer tissues, and upregulation of HABP1 was significantly associated with poor prognosis of breast cancer, including triple-negative breast cancer [12, 16]. These studies suggest that HABP1 may be a novel biomarker for the prognosis of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, HABP1 was overexpressed in breast cancer and correlated with tumor stage and lymph node metastasis 9. In addition to the abovementioned results, HABP1 was associated with histological grade, tumor size, and recurrence in triple-negative breast cancer 23. Also, HABP1 was reported to relate with histological grade, serum CA125, and FIGO stage in ovarian cancer 12.…”
Section: Discussionmentioning
confidence: 72%
“…Chen et al (2009), reported elevated levels of HABP1 mRNA and protein in breast cancer samples compared to normal breast cells and patients with low HABP1 mRNA level experienced significantly better survival rates. The study proposed that HABP1 level can act as a prognostic marker of breast cancer and elevated expression of HABP1 is related to metastasis and poor prognosis in patients [ 135 ], which is validated by further studies [ 138 , 139 ]. Later, Wang et al (2015), linked the overexpression of this protein in breast cancer tissues and its level with distant metastasis and higher histological TNM stages in triple-negative breast cancer (TNBC) specimens [ 138 ].…”
Section: The Unearthing Of Habp1mentioning
confidence: 98%
“…The study proposed that HABP1 level can act as a prognostic marker of breast cancer and elevated expression of HABP1 is related to metastasis and poor prognosis in patients [ 135 ], which is validated by further studies [ 138 , 139 ]. Later, Wang et al (2015), linked the overexpression of this protein in breast cancer tissues and its level with distant metastasis and higher histological TNM stages in triple-negative breast cancer (TNBC) specimens [ 138 ]. Multivariate analysis revealed increased expression of HABP1 is associated with cisplatin resistance, increased risk for stage III/IV via reduced overall survival (OS) and progression free survival (PFS) in advanced serous ovarian cancer patients.…”
Section: The Unearthing Of Habp1mentioning
confidence: 98%